Sexual deviance in prison: Queering identity and intimacy in prison research - Carr, Nicola (Criminology & criminal justice, 2020)
Recent years have seen increased attention in both research and policy towards lesbian, gay, bisexual and transgender prisoners as a group with distinct needs. This has been driven by wider political recognition of lesbian, gay, bisexual and transgender rights and research suggesting that lesbian, gay, bisexual and transgender prisoners are particularly ‘vulnerable’ to bullying and abuse within prison settings. Much of this research, and the policy solutions associated with it, we argue, ignores or side-steps queer perspectives, relying instead on liberal conceptions of identity, vulnerability and, ultimately, assimilation. Just as contemporary campaigns around marriage rights see lesbian, gay, bisexual and transgender communities and individuals as fundamentally the same as the majority, rather than posing a challenge to the heteronormativity of marriage as an institution, much contemporary research and policy on lesbian, gay, bisexual and transgender prisoners sees this group as marked only by potential discrimination. We argue here instead that experiences of lesbian, gay, bisexual and transgender prisoners can be read ‘queerly’ so as to potentially challenge the rigid gender and heteronormative foundations that underlie systems of incarceration. We draw on a small-scale empirical research project around the experience of lesbian, gay, bisexual and transgender prisoners to revisit contemporary paradoxes of prisons and sexuality and to problematise understandings of identity, intimacy and deviance in the prison context.